Empowering Children’s English Literacy by Listen and Do Song - Yunani Atmanegara (Jurnal Didascein Bahasa, 2016)
ABSTRACT: Song is an effective and interesting teaching tool in the classroom of language learning. It is regarded as one of the most enjoyable ways for practicing and developing English literacy of young learners. It is also useful to encourage them to be active in order to improve their skills. The purpose of this article is therefore threefold: first, theoretical discussion that presents about English literacy and young learners. Second, some suggestions of giving the selections of songs are given regarding the activities. Third, some recommended teaching instruction for listen and do song that empowers children’s English literacy. Incorporating song into language learning serves not only as an effective teaching tool but also provides a positive learning experience for young learners. Key words: English literacy, listen and do song, young learners.